Teknologi Tepat Guna TAKEDAPOT Sebagai Komponen Optimalisasi Pengembangan Rumah Pangan Lestari dan Sumber Pangan Sehat Kekebalan Tubuh di Masa Pandemi COVID-19 - Bambang Budi Santoso (Jurnal SIAR ILMUWAN TANI, 2020)
TAKEDAPOT (planting Moringa in pots) has an important meaning as a means of meeting the needs of healthy vegetables (food), providing sustainable food for at least families, as a means of preserving the resources of Moringas germplasms, as well as landscaping elements in the yard, and also can be relied upon as herbal ingredients to increase immune system which is now very much needed in connection with the COVID-19 pandemic. Intensive TAKEDAPOT planting certainly has an excess yield as an additional source of income. As a component of the optimization of the RPL (Sustainable Food Houses) program or KRPL (Sustainable Food Houses Area) TAKEDAPOT can be relied upon for the achievement of the program. With appropriate technology available TAKEDAPOT and if properly and properly implemented, at least food security will be achieved, where everyone, at all times, has physical and economic access to sufficient, safe and nutritious food, to meet their needs and preferences the food they need and as a food source for immune enhancement.